Diseño de sistema objetual terapéutico a partir de materiales cerámicos que permitan al fisioterapeuta complementar el tratamiento de artritis reumatoide en personas mayores de 40 años (2021)
Project based on the approach to the increasing problem of rheumatoid arthritis in the adult population in Colombia, which seeks to provide comprehensive treatment to patients over 40 years of age in Bogotá hand in hand with the physiotherapist. Together with Industrial Design, an objective system is developed from ceramic materials that encourages the strengthening of self-care through dynamic experiences, allowing the patient to strengthen and prolong the mobility of their joints to improve their quality of life